REFLECTIONS ON RESPONSIBILITY OF THE PROFESSIONAL OF NURSING IN THE PROCESS OF APPLICATION OF THE BACILLUS OF CALMETTE AND GUÉRIN: LITERATURE REVIEW - Oliveira, Vanessa Rodrigues de (2009)
Objective: Identify and analyze through systematic review of literature the responsibility of professional nursing in the process of implementation of BCG. Methods: Bibliographical and exploratory research, which use a qualitative approach. The search took through bibliographic and was conducted in Virtual Library of Health (LILACS, SCIELO, BDENF and MEDLINE). After collecting the data we conducted an exploratory reading, selective, analytical and interpretative. Results: The emerging categories were: professional responsibility of nursing in customer care; professional practice of nursing in customer care. Conclusion: We conclude that, when we look at the nursing assistance during the implementation of BCG-ID, realized the importance of knowing the responsibility for the team throughout the nursing process involving the application of the vaccine, so there is a total reflection and awareness of professional at all stages surrounding the relationship-enforcement responsibility. It is therefore necessary that the process of administration of the bacillus, has a significance that transposing the technical procedure.